Safety of tildrakizumab: a disproportionality analysis based on the FDA adverse event reporting system (FAERS) database from 2018-2023 - Jinger Lin; Xiangqi Chen; Min Luo; Qianwei Zhuo; Haosong Zhang; Nuo Chen; Yunqian Zhuo; Yue Han (Frontiers Media S.A., 2024)
Background: Tildrakizumab, the IL-23 inhibitor, is used to treat plaque psoriasis and psoriatic arthritis. Many studies have reported adverse drug reactions (ADRs) associated with Tildrakizumab.Objective: The aim of this study was to describe ADRs associated with Tildrakizumab monotherapy by mining data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS).Methods: The signals of Tildrakizumab-associated ADRs were quantified using disproportionality analyses such as the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multiitem gamma Poisson shrinker (MGPS) algorithms.Results: A total of 10,530,937 reports of ADRs were collected from the FAERS database, of which 1,177 reports were identified with tildrakizumab as the "primary suspect (PS)". Tildrakizumab-induced ADRs occurred against 27 system organ classes (SOCs). A total of 32 significant disproportionality Preferred Terms (PTs) conformed to the algorithms. Unexpected significant ADRs such as coronavirus infection, herpes simplex, diverticulitis, atrial fibrillation and aortic valve incompetence were also possible. The median time to onset of Tildrakizumab-associated ADRs was 194 days (interquartile range [IQR] 84-329 days), with the majority occurring, within the first 1 and 3 months after initiation of Tildrakizumab.Conclusion: This study identified a potential signal for new ADRs with Tildrakizumab, which might provide important support for clinical monitoring and risk prediction.